(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The United Nations’Millennium Development Goals (MDGs) two and three are about achieving universalprimary education and promoting gender equality, respectively. The MDGs ineducation are defined in terms of participation and completion of primaryeducation by all children and the elimination of gender discrimination ineducation. Despite the continued efforts of the various Governments onuniversalizing the primary and elementary education, through a wide range ofprogrammes and schemes, access to quality education continues to be an obstaclein the achievement of the education goals. For instance, in India, during 2004– 05, while the Gross Enrolment Ratio for children enrolling in classes I toVIII was 97 percent, the Drop-out Rate for the same classes was as high as 46percent. Recognizing this, the Government of India’s flagship educationprogramme at the primary level - the Sarva Shiksha Abhiyan (SSA) - hasstreamlined its focus on ‘quality’.